Ni-mo-cr-n alkaline seawater hydrogen evolution cathode and preparation method and application thereof
Patent Information
- Application Number
- CN202611321472.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]鉴于以上现有技术的不足之处,本发明提供了一种NiMoCrN碱性海水析氢阴极,以解决传统非贵金属阴极高电流密度海水析氢过电位高、纯Pt催化剂利用率低成本高、普通沉积法Pt易团聚、载体抗海水腐蚀与长期稳定性差等技术问题
[0021]本发明NiMoCrN碱性海水析氢阴极,通过创新性地在Cr掺杂自支撑NiMoCrN纳米活性层表面采用低浓度氯铂酸碱性电解液配合循环伏安可控电沉积策略,构筑原子级分散/极低核数团簇Pt界面耦合催化位点,不仅实现了贵金属Pt原子利用率最大化、大幅降低铂金属使用量与制氢成本,而且实现了“NiMoCrN载体水解离-界面氢中间体迁移-Pt位点氢分子生成”的协同催化反应路径,同步解决传统非贵金属阴极水解离动力学迟缓、纯Pt材料易团聚活性衰减的双重短板。这种自支撑无粘结剂的三维孔道复合结构不仅增强了电极整体导电能力、界面电子耦合强度与抗海水氯离子腐蚀稳定性,还保持了镍网基底衍生的连续开放孔道结构,保障高电流密度下电解液快速传质与析出氢气顺畅脱附,有助于电极在安培级(1.0A/cm2)碱性海水工况下长期稳定运行,600h恒电流电解维持极低驱动电压,适配光伏、风电等可再生能源耦合海水低成本制氢的工业化应用场景。
Smart Images

Figure CN122959772A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical fields of electrochemical energy materials and alkaline seawater electrolysis for hydrogen production, and particularly to an atomically platinum-modified NiMoCrN alkaline seawater hydrogen evolution cathode, its preparation method, and its application; more specifically, it relates to a NiMoCrN-Pt hydrogen evolution cathode with a NiMoCrN self-supporting electrode as a carrier, which constructs atomically Pt interface sites through cyclic voltammetric electrodeposition, as well as the preparation method of the cathode and its application in high-current-density alkaline seawater electrolysis for hydrogen production. Background Technology
[0002] Alkaline seawater electrolysis for hydrogen production can utilize abundant coastal seawater resources on-site and can be integrated with renewable energy sources such as photovoltaics and wind power, significantly reducing the dependence on freshwater resources for hydrogen production. This is a key technological route for reducing the cost of green hydrogen production and expanding hydrogen production application scenarios. However, seawater systems contain a large number of chloride ions and impurity ions, and industrial-scale electrolysis typically requires an efficiency of 1.0 A / cm². 2 Long-term operation at high current densities places stringent requirements on the catalytic activity, corrosion resistance, gas-liquid mass transfer performance, and long-term stability of the hydrogen evolution cathode.
[0003] NiMo-based nitrides, with their excellent alkaline water-splitting ability and good conductivity, are highly promising non-precious metal hydrogen evolution catalysts. Introducing Cr and N elements into the NiMo system can regulate the electronic structure of the material, improving corrosion resistance and intrinsic catalytic activity to some extent. However, under ampere-level high current density alkaline seawater conditions, the water dissociation kinetics of pure NiMoCrN materials are limited, the driving potential required for the hydrogen evolution reaction is relatively high, and the conversion efficiency of hydrogen intermediates is insufficient, making it difficult to meet the demand for low-energy hydrogen production.
[0004] Platinum (Pt) possesses a near-ideal hydrogen adsorption free energy, making it a recognized highly efficient hydrogen evolution catalyst. Traditional commercial Pt-based catalysts are mostly particulate Pt, which suffers from drawbacks such as high precious metal loading, extremely low atom utilization, and high preparation costs. Conventional potentiostatic deposition and impregnation reduction methods easily cause Pt to rapidly agglomerate and grow, forming large-sized crystalline particles. This not only further wastes precious metals but also clogs the pores on the catalyst surface, hindering electrolyte penetration and hydrogen desorption, and exacerbating polarization losses at high current densities.
[0005] The alkaline hydrogen evolution reaction consists of two steps: water molecule dissociation and hydrogen intermediate adsorption / desorption. A single Pt site can only efficiently complete H* conversion, lacking the ability to activate water molecules. Ordinary Cr-free NiMo nitride supports have weak electronic regulation capabilities, making it difficult to stably anchor noble metal atoms. It is also difficult to form an effective electronic cooperation interface between the noble metal and the support, leading to problems such as noble metal detachment and support corrosion and pulverization during long-term electrolysis. At the same time, traditional noble metal deposition processes cannot precisely control the nucleation and growth behavior of Pt, making it difficult to achieve atomic-level uniform dispersion of Pt. This makes it impossible to balance high catalytic activity, low Pt dosage, and electrode pore permeability, limiting the industrial application of seawater electrolysis cathodes. Summary of the Invention
[0006] In view of the shortcomings of the prior art, the present invention provides a NiMoCrN alkaline seawater hydrogen evolution cathode to solve the technical problems of high overpotential of high current density seawater hydrogen evolution in traditional non-precious metal cathodes, high utilization rate and low cost of pure Pt catalyst, easy agglomeration of Pt in ordinary deposition method, and poor resistance to seawater corrosion and long-term stability of the support.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] A NiMoCrN alkaline seawater hydrogen evolution cathode, the cathode comprising a nickel mesh substrate, an in-situ supported NiMoCrN active layer on the surface of the nickel mesh substrate, and Pt active sites dispersed on the surface of the NiMoCrN active layer; the Pt active sites exist in the form of isolated atoms, atomically dispersed states, or extremely low nucleus cluster states, and form an interfacial coupled catalytic region with the Cr-containing NiMoCrN surface.
[0009] As a preferred technical solution, the NiMoCrN active layer is composed of nanorods, short rods, bulk particles or combinations thereof, continuously covering the surface of the nickel mesh and retaining open channels; Pt, Cr, Mo, Ni and N are dispersed in the active layer.
[0010] Another aspect of the present invention is to provide a method for preparing the NiMoCrN alkaline seawater hydrogen evolution cathode as described above, the method comprising the following steps:
[0011] S1: Provide a nickel mesh substrate, and prepare a self-supporting NiMoCrN active layer electrode on the surface of the nickel mesh substrate by in-situ loading via hydrothermal reaction;
[0012] S2: Prepare an alkaline electrodeposition solution containing KOH and H2PtCl6; and use a three-electrode system, with the NiMoCrN active layer electrode obtained in step S1 as the working electrode, the graphite rod as the counter electrode, and the Hg / HgO electrode as the reference electrode, to electrodeposit Pt on the surface of the NiMoCrN active layer electrode by cyclic voltammetry to obtain the NiMoCrN alkaline seawater hydrogen evolution cathode.
[0013] As a preferred technical solution, in step S1, the in-situ loading method of the hydrothermal reaction specifically includes the following steps: preparing a mixture of 0.03–0.07 M Ni(NO3)2·6H2O and 0.01–0.03 M (NH4)6Mo7O 24 A hydrothermal reaction solution composed of 4H2O and 1-3 mM CrCl3·6H2O was used to grow a NiMoCr precursor in situ on a nickel mesh substrate using hydrothermal reaction. Urea was used as the nitrogen source, and nitriding was carried out in an N2 atmosphere. The hydrothermal reaction was carried out at a temperature of 200℃. During the nitriding operation, the amount of urea used was 0.05-0.15 g / mL relative to the hydrothermal reaction solution, and the temperature was increased to 350-450℃ at a rate of 1-3℃ / min and held for 2-5 hours.
[0014] As a preferred technical solution, in step S2, the electrodeposition solution is composed of 0.5-1.5M KOH and 0.05-0.25mmol / L H2PtCl6.
[0015] As a preferred technical solution, in step S2, the scanning potential range of the cyclic voltammetry is 0.05 to -0.50V, relative to the reversible hydrogen electrode; the scanning rate is 4 to 6mV / s, preferably 5mV / s.
[0016] As a preferred technical solution, in step S2, the number of scan cycles for the cyclic voltammetry is 70.
[0017] Another aspect of the present invention is to provide an application of a NiMoCrN alkaline seawater hydrogen evolution cathode, wherein the NiMoCrN alkaline seawater hydrogen evolution cathode as described above is used for alkaline seawater electrolysis to produce hydrogen, and it operates in an electrolyte containing 0.5 to 1.5 M NaOH and natural seawater.
[0018] As a preferred technical solution, the alkaline seawater electrolysis hydrogen production process operates at 1.0 A / cm². 2 It operates under constant current conditions and has a stable operating time of ≥600 hours.
[0019] As a preferred technical solution, the NiMoCrN alkaline seawater hydrogen evolution cathode, anode, and electrolyte are configured into an alkaline seawater electrolysis cell; the electrolyte includes 0.5-1.5M NaOH and natural seawater.
[0020] The beneficial effects of this invention are:
[0021] This invention relates to a NiMoCrN alkaline seawater hydrogen evolution cathode. Through an innovative approach, a low-concentration chloroplatinic acid alkaline electrolyte combined with a cyclic voltammetry-controlled electrodeposition strategy is employed on the surface of a Cr-doped self-supporting NiMoCrN nanolayer to construct atomically dispersed / extremely low-nucleus-number clusters of Pt interfacial coupled catalytic sites. This not only maximizes the utilization rate of precious metal Pt atoms and significantly reduces platinum usage and hydrogen production costs, but also achieves a synergistic catalytic reaction pathway of "NiMoCrN support water dissociation - interfacial hydrogen intermediate migration - Pt site hydrogen molecule generation," simultaneously addressing the dual shortcomings of traditional non-precious metal cathodes: slow water dissociation kinetics and easy agglomeration and activity decay of pure Pt materials. This self-supporting, binder-free three-dimensional porous composite structure not only enhances the overall conductivity of the electrode, the interfacial electronic coupling strength, and the stability against seawater chloride ion corrosion, but also maintains the continuous open porous structure derived from the nickel mesh substrate, ensuring rapid mass transfer of the electrolyte and smooth desorption of evolved hydrogen at high current densities. This contributes to the electrode's performance at ampere levels (1.0 A / cm²). 2 It can operate stably for a long time under alkaline seawater conditions, and maintain an extremely low driving voltage through 600 hours of constant current electrolysis, making it suitable for industrial applications that couple renewable energy sources such as photovoltaic and wind power with seawater for low-cost hydrogen production. Attached Figure Description
[0022] Figure 1 This is a low-magnification scanning electron microscope image of the NiMoCrN-Pt-70cycle cathode prepared in Example 1 of the present invention on a nickel grid.
[0023] Figure 2 This is a high-magnification scanning electron microscope image of the NiMoCrN-Pt-70cycle cathode prepared in Example 1 of the present invention.
[0024] Figure 3 This is a transmission electron microscope image of the NiMoCrN-Pt-70cycle cathode prepared in Example 1 of the present invention.
[0025] Figure 4 This is a high-angle annular dark-field scanning transmission electron microscope image of the NiMoCrN-Pt-70cycle cathode prepared in Example 1 of this invention, with spherical aberration correction.
[0026] Figure 5 a to Figure 5 f is the total elemental superposition diagram and the surface distribution diagram of Cr, Mo, Ni, N and Pt elements of the NiMoCrN-Pt-70cycle cathode prepared in Example 1 of the present invention.
[0027] Figure 6 The X-ray diffraction pattern of the NiMoCrN-Pt-70cycle cathode prepared in Example 1 of this invention is shown.
[0028] Figure 7 The full X-ray photoelectron spectrum of the NiMoCrN-Pt-70cycle cathode prepared in Example 1 of this invention is shown.
[0029] Figure 8 The hydrogen evolution polarization curves of NiMoCrN-Pt, NiMoCrN, NiMoN, NiMoCr and NiMo with different Pt electrodeposition cycles prepared in Example 1 and Comparative Examples 1-6 of this invention are shown.
[0030] Figure 9 Electrolytic cells employing NiMoCrN-Pt, NiMoCrN, and NiMoN cathodes were used in a 1M NaOH and seawater electrolyte at a flow rate of 1.0 A / cm. 2 Stability comparison chart under constant current. Detailed Implementation
[0031] The following description is intended to disclose the invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious variations will occur to those skilled in the art.
[0032] Example 1
[0033] This embodiment provides a NiMoCrN alkaline seawater hydrogen evolution cathode (denoted as NiMoCrN-Pt-70cycle electrode), the preparation method of which includes the following steps:
[0034] S1 Preparation of self-supporting NiMoCrN active layer electrode: A nickel mesh with a thickness of 0.5 mm, a mesh size of 46 mesh, and a wire diameter of 0.25 mm was selected and cut into 5 cm × 5 cm pieces. The mesh was then ultrasonically cleaned sequentially in 10% hydrochloric acid aqueous solution, acetone, anhydrous ethanol, and deionized water for 30 min each. After each ultrasonic cleaning, the mesh was thoroughly rinsed with deionized water and finally dried for later use. Ni(NO3)2·6H2O and (NH4)6Mo7O were added to 35 mL of deionized water. 24·4H2O and CrCl3·6H2O were mixed to achieve final concentrations of 0.05M, 0.02M, and 2mM, respectively. The mixture was magnetically stirred for 1 hour until completely dissolved to obtain a hydrothermal reaction solution. The pretreated nickel mesh was placed vertically in a 50mL polytetrafluoroethylene-lined hydrothermal reactor, and the above reaction solution was added. After sealing, the reactor was hydrothermally reacted at 200℃ for 7 hours. The reactor was then cooled, cleaned, and dried to obtain the NiMoCr precursor. 3g of urea was placed upstream of the gas flow in a tubular furnace, and the NiMoCr precursor was placed downstream. High-purity N2 was continuously introduced at a rate of 200mL / min, and the temperature was increased from room temperature to 400℃ at a rate of 2℃ / min and held for 3 hours for nitriding treatment. The reactor was then naturally cooled to room temperature in an N2 atmosphere to obtain a self-supporting NiMoCrN electrode. The electrode surface was in situ loaded with a NiMoCrN active layer that continuously covered the nickel mesh and retained three-dimensional open channels.
[0035] S2 Cyclic Voltammetric Electrodeposition of Atomic-Grade Pt: An aqueous solution containing 1M KOH and 0.15mM H2PtCl6 was prepared as the electrodeposition solution and thoroughly mixed by magnetic stirring. A standard three-electrode system was used, with the NiMoCrN electrode obtained in step S1 as the working electrode, a graphite rod as the counter electrode, and an Hg / HgO electrode as the reference electrode. Cyclic voltammetry was performed in the above electrodeposition solution, with a scanning potential window of 0.05V to -0.50V (relative to the reversible hydrogen electrode RHE), a scanning rate of 5mV / s, and 70 consecutive cycles. During the scanning process, Pt precursor ions were gradually reduced and deposited on the NiMoCrN surface in the cathode potential range. After deposition, the working electrode was removed, rinsed with deionized water, and dried to obtain the NiMoCrN alkaline seawater hydrogen evolution cathode. The Pt active sites were dispersed on the surface of the Cr-containing NiMoCrN active layer in the form of isolated atoms, atomic-level dispersion, or extremely low nucleus clusters, and formed an interfacial coupled catalytic region with the support.
[0036] Test results show that: Figure 1 As shown, the active layer of the NiMoCrN-Pt-70cycle cathode continuously covers the surface of the nickel mesh wire. The inherent three-dimensional braided structure and open channels of the nickel mesh remain intact after electrodeposition, indicating that the cyclic voltammetric electrodeposition process does not destroy the self-supporting skeleton and can maintain electrolyte flow and gas exhaust channels under high current density. Figure 2 High-magnification SEM images show that the active layer consists of radial short rods, blocky particles, and coarse clusters, with obvious gaps between the particles. Compared with the NiMoCrN morphology before electrodeposition, no large-scale continuous Pt capping layer was observed, indicating that Pt deposition did not completely seal the pores of the active layer. Figure 3TEM images show that the NiMoCrN-Pt active material is composed of nanocrystals and locally disordered regions. No large Pt crystals with obvious size and clear boundaries were found, indicating that Pt mainly exists in a highly dispersed state on or near the surface of NiMoCrN. Figure 4 Scattered bright spots are visible in the aberration-corrected high-angle annular dark-field scanning transmission electron microscope image. Since the HAADF signal intensity is highly correlated with the atomic number, combined with the high atomic number characteristics of Pt in the sample, the discrete bright spots can be attributed to atomic-level Pt sites or extremely low nucleus number Pt structures. No continuous bright lattice regions are seen in the image. This invention uses "atomic-level Pt" to describe the discrete bright Pt active sites, which exist in any form: isolated atoms, atomic-level dispersion (interspersed atomic-level Pt sites), or extremely low nucleus number clusters (extremely low nucleus number Pt structures that do not form identifiable bulk grains). Figure 5 a to Figure 5 The elemental distribution map of f shows that Cr, Mo, Ni, and N are uniformly dispersed in the active layer, while the Pt signal is distributed as discrete points covering the same nanoscale region. Pt does not form a continuous enrichment region, indicating that low-concentration precursors and controlled cyclic voltammetry are beneficial for suppressing large-scale Pt aggregation. The co-spatial distribution of Pt and Cr in the same NiMoCrN active layer provides structural conditions for interfacial electronic coupling. Cr is not the main active center in this application, but an important regulatory component of the NiMoCrN support. Its role is to change the local coordination and electronic environment of the support, thereby facilitating the stability of Pt sites and interfacial synergy. Figure 6 The X-ray diffraction pattern showed that the diffraction characteristics of NiMoCrN and the nickel mesh substrate were preserved, and no identifiable bulk Pt characteristic peaks were found. This result is consistent with the spherical aberration-corrected electron microscopy and Pt elemental distribution, indicating that the Pt loading is low and the dispersion is high. Figure 7 The XPS full spectrum clearly identifies Pt4f, Mo3d, C1s, N1s, Cr2p, and Ni2p related signals, proving that Pt has been introduced into an active layer containing Ni, Mo, Cr, and N. The XPS full spectrum is used to confirm the elemental composition, but it is not used to determine the precise valence state of Pt and the Pt-Cr bond type separately. The conclusion that Pt is atomically dispersed is mainly supported by spherical aberration-corrected electron microscopy, Pt elemental distribution, and the absence of bulk Pt peaks in XRD.
[0037] Comparative Example 1:
[0038] The NiMoCrN alkaline seawater hydrogen evolution cathode of this comparative example has the same raw material composition and preparation steps as Example 1. The difference is that in the preparation method of this comparative example, the number of cyclic voltammetry scans is adjusted to 40 cycles to obtain the NiMoCrN-Pt-40cycle electrode.
[0039] Comparative Example 2:
[0040] The NiMoCrN alkaline seawater hydrogen evolution cathode of this comparative example has the same raw material composition and preparation steps as Example 1. The difference is that in the preparation method of this comparative example, the number of cyclic voltammetry scans is adjusted to 100 cycles to obtain the NiMoCrN-Pt-100cycle electrode.
[0041] Comparative Example 3:
[0042] The NiMoCrN alkaline seawater hydrogen evolution cathode of this comparative example has the same raw material composition and preparation steps as Example 1. The difference is that the preparation method of this comparative example does not perform step S2 cyclic voltammetric electrodeposition of atomic-level Pt.
[0043] Comparative Example 4:
[0044] The alkaline seawater hydrogen evolution cathode of this comparative example has the same raw material composition and preparation steps as Example 1. The difference is that in the preparation method of this comparative example, CrCl3·6H2O was not added to the hydrothermal reaction solution in step S1 to carry out the hydrothermal reaction, and the resulting alkaline seawater hydrogen evolution cathode was denoted as NiMoN electrode.
[0045] Comparative Example 5:
[0046] The alkaline seawater hydrogen evolution cathode of this comparative example has the same raw material composition and preparation steps as Example 1. The difference is that in the preparation method of this comparative example, urea was not added for nitriding treatment in step S1 to obtain the alkaline seawater hydrogen evolution cathode, which is denoted as NiMoCr electrode.
[0047] Comparative Example 6:
[0048] The NiMoCrN alkaline seawater hydrogen evolution cathode of this comparative example has the same raw material composition and preparation steps as Example 1. The difference is that in the preparation method of this comparative example, CrCl3·6H2O was not added to the hydrothermal reaction solution in step S1 for hydrothermal reaction, and urea was not added in step S1 for nitriding treatment, thus obtaining an alkaline seawater hydrogen evolution cathode, denoted as NiMo electrode.
[0049] Hydrogen evolution polarization curve testing and comparative analysis:
[0050] In an electrolyte prepared with natural seawater as solvent and NaOH concentration of 1M, a three-electrode system was used. Different cathodes prepared in Example 1 and Comparative Examples 1-6 were used as working electrodes, graphite rods as counter electrodes, and Hg / HgO electrodes as reference electrodes. Linear scan voltammetry was performed at a scan rate of 5mV / s, and the hydrogen evolution polarization curves of each electrode were recorded.
[0051] like Figure 8As shown, the NiMoCrN-Pt-70cycle electrode prepared in Example 1 exhibits high current density across the entire high current density range (-300 to -1000 mA / cm²). 2 All samples exhibited the lowest cathodic polarization, and their hydrogen evolution activity was significantly higher than that of all control samples in Comparative Examples 1-6. Specifically: Although Comparative Example 1 (40 cycles) and Comparative Example 2 (100 cycles) were also loaded with Pt, the activity of the 70-cycle sample was superior to both, indicating that 70 cycles is the optimal number of deposition cycles; Comparative Example 3 (NiMoCrN without Pt loading) showed a significantly lower current density at the same potential than the 70-cycle sample, indicating that the introduction of Pt sites plays a key role in reducing the hydrogen evolution overpotential; the hydrogen evolution activity of Comparative Example 4 (NiMoN, without Cr) and Comparative Example 5 (NiMoCr, without nitriding) decreased sequentially, indicating that both Cr doping and the introduction of N elements can improve the intrinsic hydrogen evolution performance of NiMo-based materials; Comparative Example 6 (NiMo, without Cr and without nitriding) showed the highest hydrogen evolution overpotential and the lowest current density among all samples, further confirming the important role of synergistic regulation of Cr and N in improving catalytic activity.
[0052] Depend on Figure 8 Reading reaches -1000mA / cm 2 The potentials at 40, 70, and 100 cycles, as shown in Table 1, are approximately -0.24V, -0.11V, and -0.14V, respectively, relative to RHE. This result indicates that 70 cycles of deposition resulted in a more suitable Pt site density and interface state.
[0053] Table 1
[0054] sample Cyclic voltammetry cycles <![CDATA[reaching −1000mA / cm 2 potential at this time (V vs. RHE)]]> Activity evaluation NiMoCrN-Pt-40cycle 40 Approximately -0.24 The number of Pt sites is relatively insufficient. NiMoCrN-Pt-70cycle 70 Approximately -0.11 Optimal activity NiMoCrN-Pt-100cycle 100 Approximately -0.14 Increasing the number of laps did not further improve activity.
[0055] The above potential values are from Figure 8 The polarization curves shown illustrate the effect of the number of cyclic voltammetry deposition cycles on the hydrogen evolution performance of NiMoCrN-Pt. Since the precursor concentration, scan range, and scan rate are the same for 40, 70, and 100 cycles, the performance differences can be attributed to the variation of Pt deposition amount and dispersion state with the number of cycles.
[0056] Example 2 (Application Example)
[0057] The NiMoCrN-Pt-70cycle cathode prepared in Example 1 was used as the hydrogen evolution cathode in alkaline seawater electrolysis. It was assembled with the alkaline oxygen evolution anode (using a commercially available 2cm*2cm Raney Ni mesh) to form an alkaline seawater electrolysis cell. The electrolyte was prepared using natural seawater (taken from the coastal waters of Ningbo and filtered through a 0.45μm microporous membrane to remove suspended solids) as the solvent. Sodium hydroxide (NaOH) was added and fully dissolved to obtain an alkaline seawater electrolyte with a final NaOH concentration of 1.0 mol / L. A constant current mode was used at 1.0 A / cm². 2 Long-term constant current electrolysis tests were conducted at high current densities, and the change curve of the total voltage of the electrolytic cell over time was recorded. Comparative tests were performed under the same conditions using a NiMoCrN cathode without Pt deposition (Comparative Example 3) and a NiMoN cathode without Cr (Comparative Example 4). It should be noted that electrochemical workstation calibration, electrode area limitation, iR compensation, sample cleaning, and routine characterization steps not detailed in this invention can be performed using methods commonly used in the art.
[0058] Test results show that, Figure 9 As shown in Table 2, the electrolytic cell using the NiMoCrN-Pt-70cycle cathode maintained a voltage of approximately -1.90V during 600 hours of continuous operation, without exhibiting a sustained voltage increase trend. In contrast, the control electrolytic cell using an unloaded Pt NiMoCrN cathode had a voltage of approximately -2.15V under the same conditions, about 250mV higher than the NiMoCrN-Pt-70cycle cell. The control electrolytic cell using a Cr-free NiMoN cathode showed a rapid negative voltage shift and significant polarization early in the testing process, indicating rapid deactivation in a high-current-density, chlorine-containing alkaline environment. Based on the absolute value of the tested voltage, the NiMoCrN-Pt electrolytic cell required the lowest driving voltage.
[0059] Table 2
[0060] sample Current density Test time Stability performance NiMoCrN-Pt-70cycle <![CDATA[1.0A / cm 2 ]]> 600h The voltage is approximately -1.90V and remains stable over a long period. NiMoCrN <![CDATA[1.0A / cm 2 ]]> 600h The voltage is approximately -2.15V, while the driving voltage is relatively high. NiMoN <![CDATA[1.0A / cm 2 ]]> Early instability Rapid negative voltage shift
[0061] Figure 9 The results in Table 2 show that the electrolytic cell using NiMoCrN-Pt cathode did not exhibit a sustained rapid pressure increase during long-term operation, indicating that the atomic-level Pt sites can remain effective under conditions of salt-containing alkaline electrolyte and high bubble flux; the NiMoCrN self-supporting framework provides mechanical support and continuous conductive channels.
[0062] Furthermore, combined Figures 4 to 9It can be seen that Pt is loaded in a highly dispersed state on the Cr-regulated NiMoCrN surface, and the sample with 70 deposition cycles exhibits the best hydrogen evolution activity and the lowest long-term driving voltage. Based on this, it can be inferred that the Ni, Mo, Cr, and N / O local sites on the NiMoCrN surface preferentially participate in water molecule adsorption and dissociation. The generated H* or hydrogen-containing intermediates are transferred to adjacent Pt sites, and the Pt sites further promote the electrochemical desorption or recombination of H* to form H2. 2 In this invention, the interaction between Pt and Cr is manifested as the Pt site regulating the interfacial electronic coupling of the support, rather than Cr being the main hydrogen evolution center of this invention; Cr alters the local electronic distribution and coordination heterogeneity of the NiMoCrN support, while Pt undertakes the main function of efficient hydrogen intermediate conversion, and the two work together to reduce the driving potential required for ampere-level hydrogen evolution.
[0063] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A NiMoCrN alkaline seawater hydrogen evolution cathode, characterized in that, The cathode includes a nickel mesh substrate, an in-situ supported NiMoCrN active layer on the surface of the nickel mesh substrate, and Pt active sites dispersed on the surface of the NiMoCrN active layer. The Pt active sites exist in the form of isolated atoms, atomic-level dispersion, or extremely low nucleus clusters, and form an interfacial coupled catalytic region with the Cr-containing NiMoCrN surface.
2. The NiMoCrN alkaline seawater hydrogen evolution cathode as described in claim 1, characterized in that, The NiMoCrN active layer is composed of nanorods, short rods, bulk particles or combinations thereof, continuously covering the surface of the nickel mesh and retaining open channels; Pt, Cr, Mo, Ni and N are dispersed in the active layer.
3. A method for preparing a NiMoCrN alkaline seawater hydrogen evolution cathode as described in claim 1 or 2, characterized in that, The preparation method includes the following steps: S1: Provide a nickel mesh substrate, and prepare a self-supporting NiMoCrN active layer electrode on the surface of the nickel mesh substrate by in-situ loading via hydrothermal reaction; S2: Prepare an alkaline electrodeposition solution containing KOH and H2PtCl6; and use a three-electrode system, with the NiMoCrN active layer electrode obtained in step S1 as the working electrode, the graphite rod as the counter electrode, and the Hg / HgO electrode as the reference electrode, to electrodeposit Pt on the surface of the NiMoCrN active layer electrode by cyclic voltammetry to obtain the NiMoCrN alkaline seawater hydrogen evolution cathode.
4. The method for preparing the NiMoCrN alkaline seawater hydrogen evolution cathode as described in claim 3, characterized in that, In step S1, the in-situ hydrothermal reaction loading method specifically includes the following steps: preparing a mixture of 0.03–0.07 M Ni(NO3)2·6H2O and 0.01–0.03 M (NH4)6Mo7O 24 A hydrothermal reaction solution composed of 4H2O and 1-3 mM CrCl3·6H2O was used to grow a NiMoCr precursor in situ on a nickel mesh substrate using hydrothermal reaction. Urea was used as the nitrogen source, and nitriding was carried out in an N2 atmosphere. The hydrothermal reaction was carried out at a temperature of 200℃. During the nitriding operation, the amount of urea used was 0.05-0.15 g / mL relative to the hydrothermal reaction solution, and the temperature was increased to 350-450℃ at a rate of 1-3℃ / min and held for 2-5 hours.
5. The method for preparing the NiMoCrN alkaline seawater hydrogen evolution cathode as described in claim 3, characterized in that, In step S2, the electrodeposition solution consists of 0.5–1.5 M KOH and 0.05–0.25 mmol / L H2PtCl6.
6. The method for preparing the NiMoCrN alkaline seawater hydrogen evolution cathode as described in claim 3, characterized in that, In step S2, the scanning potential range of the cyclic voltammetry is 0.05 to -0.50 V, relative to the reversible hydrogen electrode; the scanning rate is 4 to 6 mV / s, preferably 5 mV / s.
7. The method for preparing the NiMoCrN alkaline seawater hydrogen evolution cathode as described in claim 1, characterized in that, In step S2, the number of scans for the cyclic voltammetry is 70.
8. An application of a NiMoCrN alkaline seawater hydrogen evolution cathode, characterized in that, The NiMoCrN alkaline seawater hydrogen evolution cathode as described in claim 1 or 2 is used for alkaline seawater electrolysis to produce hydrogen, so that it operates in an electrolyte containing 0.5 to 1.5 M NaOH and natural seawater.
9. The application of the NiMoCrN alkaline seawater hydrogen evolution cathode as described in claim 8, characterized in that, The alkaline seawater electrolysis hydrogen production process is carried out at 1.0 A / cm. 2 It operates under constant current conditions and has a stable operating time of ≥600 hours.
10. The application of the NiMoCrN alkaline seawater hydrogen evolution cathode as described in claim 8, characterized in that, The NiMoCrN alkaline seawater hydrogen evolution cathode and anode, along with the electrolyte, are configured to form an alkaline seawater electrolysis cell; the electrolyte comprises 0.5–1.5 M NaOH and natural seawater.